2020
DOI: 10.1002/cmdc.202000368
|View full text |Cite
|
Sign up to set email alerts
|

ACE2, the Receptor that Enables Infection by SARS‐CoV‐2: Biochemistry, Structure, Allostery and Evaluation of the Potential Development of ACE2 Modulators

Abstract: Angiotensin converting enzyme 2 (ACE2) is the human receptor that interacts with the spike protein of coronaviruses, including the one that produced the 2020 coronavirus pandemic (COVID‐19). Thus, ACE2 is a potential target for drugs that disrupt the interaction of human cells with SARS‐CoV‐2 to abolish infection. There is also interest in drugs that inhibit or activate ACE2, that is, for cardiovascular disorders or colitis. Compounds binding at alternative sites could allosterically affect the interaction wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 73 publications
3
44
0
Order By: Relevance
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Long-duration modeling can also be applied to in silico screening of molecules that could inhibit the S RBD-ACE2 interaction 8,9,33 . These may be antibodies, peptides or small molecules that either bind directly to the interaction surface or act allosterically to stabilize S RBD in a conformation with low ACE2 binding affinity.…”
Section: Application Of Millisecond-scale MD Simulation To Design Of mentioning
confidence: 99%
“…Our findings reveal that free S RBD has assumed an optimized ACE2 binding-ready conformation, incurring little entropic penalty for binding, an evolutionary adaptation that contributes to its high affinity for the receptor 6 . We further identified high probability molecular binding interactions that inform both vaccine design and therapeutic development, which may include recombinant ACE2-based spike decoys 7 and/or allosteric S RBD-ACE2 binding inhibitors 8,9 to prevent or arrest infection and thus disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies reported the effect of binding of some molecules to ACE2 in the closed conformation on the affinity of ACE2 for the SARS spike. 80 , 81 They proposed such drug–ACE2 interactions may decrease ACE2 affinity for the SARS spike. They also postulated the critical role of the closed, substrate-bonded state of ACE2 in its binding to SARS or the COVID-19 virus spike protein.…”
Section: Resultsmentioning
confidence: 99%
“…Blockade of ACE2 receptor could be achieved through specific antibodies (Li et al, 2003), rationally designed small molecules (Dales et al, 2002;Huentelman et al, 2004;Gross et al, 2020;Pillaiyar et al, 2020) or peptides (Huang et al, 2003). Although their efficacy needs to be confirmed, some of these agents are currently available on the market and have been show to effectively block SARS-CoV invasion (Li S.-R. et al, 2020).…”
Section: Ace2 Blockersmentioning
confidence: 99%